Taxonomic notes on the genus Furcaperla (Plecoptera: Perlidae) from China - Yan, Yanhua; Li, Mengyu; Li, Weihai (Zootaxa, 2021)
Two species of the genus Furcaperla Sivec 1988 (in: Sivec et al. 1988), F. bifurcata (Wu, 1948) and F. jiangxiensis Yang & Yang, 1991 are illustrated and redescribed. The taxonomic relationship of F. bifurcata and F. jiangxiensis is discussed. An unassociated female from Guangxi Zhuang Autonomous Region, Furcaperla Cn-G is described under informal designation. The first record for F. jiangxiensis from Fujian Province is given.